PERANCANGAN DESAIN UI/UX PADA APLIKASI SIPOND (SISTEM INFORMASI PONDOK) DENGAN MENGGUNAKAN METODE AGILE UX (USER EXPERIENCE) DI POPES MODERN DAREL AZHAR - Muhamad Iqbal Mandala Putra; Sofa Sofiana (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Darel Azhar modern Islamic boarding school is one of the pesantren-based educational institutions in Rangkasbitung, Lebak, Banten and has been established since 1995. Darel Azhar's modern Islamic boarding school itself is not only a boarding school that teaches religious knowledge but in it there are also educational units according to national education levels starting from MTs, SMA and Aliyah. One of the technology-based information services available at Darel Azhar's modern Islamic boarding school is SIPOND (Islamic Boarding School Information System). SIPond is a boarding school application or school application that runs online and in real time. However, there are still many guardians of students who have not used this application. Based on the results of interviews using a small up front analysis method to the person in charge of Sipond and also interviews with 5 guardians of students, it was found that this application still needs development in terms of design. The purpose of this study is to understand user needs in designing and producing mobile prototypes that pay attention to UI/UX aspects. The method used in this study is the Agile UX method with sprint stages commonly used in scrum. Keywords: Information Systems, Mobile Applications, Agile UX, Scrum, User Interface, User Experience.